2018
DOI: 10.1111/nyas.13701
|View full text |Cite
|
Sign up to set email alerts
|

Is auditory perceptual timing a core deficit of developmental coordination disorder?

Abstract: Time is an essential dimension for perceiving and processing auditory events, and for planning and producing motor behaviors. Developmental coordination disorder (DCD) is a neurodevelopmental disorder affecting 5–6% of children that is characterized by deficits in motor skills. Studies show that children with DCD have motor timing and sensorimotor timing deficits. We suggest that auditory perceptual timing deficits may also be core characteristics of DCD. This idea is consistent with evidence from several doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 95 publications
4
34
0
Order By: Relevance
“…Moreover, in line with the recent proposition of Trainor et al. (2018), it is possible that the general—effector‐independent and modality‐independent—deficit in SMS could result from a deficit in timing perception.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, in line with the recent proposition of Trainor et al. (2018), it is possible that the general—effector‐independent and modality‐independent—deficit in SMS could result from a deficit in timing perception.…”
Section: Discussionsupporting
confidence: 63%
“…Sensorimotor timing has been proposed as a central deficit of developmental coordination disorder (DCD), which is a neurodevelopmental disorder characterized by impaired motor skills and affecting about 5%–6% of school‐aged children (American Psychiatric Association, 2013; Trainor, Chang, Cairney, & Li, 2018; Wilson et al., 2017). Accordingly, previous studies showed that sensorimotor synchronization in children with DCD is less stable than in children with typical development (TD; De Castelnau, Albaret, Chaix, & Zanone, 2007, 2008; Debrabant, Gheysen, Caeyenberghs, Van Waelvelde, & Vingerhoets, 2013; MacKenzie et al., 2008; Roche, Viswanathan, Clark, & Whitall, 2016; Whitall et al., 2006, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that children with DCD would have more difficulties synchronizing, learning, retaining, and reactivating a new temporal sensorimotor sequence than TD children. Moreover, we expected that difficulties would be modulated by the sensory modality of the stimuli, with a greater learning deficit for auditory than visual stimuli, as per the hypothesis of Trainor et al (2018). Our results were partially consistent with our hypotheses.…”
Section: Discussionsupporting
confidence: 86%
“…On this basis, this study aims to test the hypothesis for a specific audio-motor coupling impairment using manual responses in DCD when learning, retaining, and reactivating a new temporal sequence presented with either auditory or visual stimuli. In accordance with the hypothesis of an auditory timing deficit (Trainor et al, 2018), we expected that, compared to TD children, DCD children would have a deficit in SMS, learning, retention, and reactivation for a new audio-motor temporal sequence compared to a new visuo-motor temporal sequence. More operationally, we expected children with DCD to demonstrate a lesser decrease in mean asynchrony (and a lesser increase in stability) when practicing the audio-motor sequence compared to the visuo-motor temporal sequence.…”
Section: Introductionmentioning
confidence: 76%
“…However, all of these studies investigated performance in rhythm production tasks, which may be easily affected by inherent motor coordination deficits. Only Trainor et al (2018) have investigated auditory timing with perceptual tasks in DCD; their first behavioral and neuroimaging evidence suggest that auditory perceptual timing (measured with duration and rhythmic discrimination tasks) may also be impaired in this population. Interestingly, motor impairments in children with DCD have also been associated with difficulties in language processing ( Mirabella et al, 2017 ).…”
Section: Atypical Rhythm In Children With Atypical Speech/language Dementioning
confidence: 99%